2006
DOI: 10.1021/es061402v
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Cyanide Exhaust Emissions from In-Use Motor Vehicles

Abstract: Motor vehicle exhaust emissions are known to contain hydrogen cyanide (HCN), but emission rate data are scarce and, in the case of idling vehicles, date back over 20 years. For the first time, vehicular HCN exhaust emissions from a modern, in-use fleet at idle have been measured. The 14 tested light duty motor vehicles were operating at idle as these conditions are associated with the highest risk exposure scenarios (i.e., enclosed spaces). Vehicular HCN was detected in 89% of the sampled exhaust streams and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…EPA, 2010b). HCN has been reported previously in vehicle exhaust (Bradow and Stump, 1977;Keirns and Holt, 1978;Cadle et al, 1979;Garbe, 1979, 1980;Karlsson, 2004;Baum et al, 2007;Moussa et al, 2016). It may form over the catalytic converters in the vehicle emission control systems (Voorhoeve et al, 1975;Suárez and Löffler, 1986;Baum et al, 2007).…”
Section: Hcnmentioning
confidence: 88%
“…EPA, 2010b). HCN has been reported previously in vehicle exhaust (Bradow and Stump, 1977;Keirns and Holt, 1978;Cadle et al, 1979;Garbe, 1979, 1980;Karlsson, 2004;Baum et al, 2007;Moussa et al, 2016). It may form over the catalytic converters in the vehicle emission control systems (Voorhoeve et al, 1975;Suárez and Löffler, 1986;Baum et al, 2007).…”
Section: Hcnmentioning
confidence: 88%
“…Small amounts of HCN (∼0.01 Tg N yr −1 ) are released into the atmosphere from gold mining (Korte and Coulston, 1998). HCN exhaust emissions from vehicles are small (Baum et al, 2007;Karlsson, 2004). Li et al (2003) argued that enhanced HCN observed in the Chinese urban plumes during TRACE-P could indicate an HCN source from hard coal burning.…”
Section: Sources Of Hcnmentioning
confidence: 99%
“…Hydrogen cyanide (HCN) is a colourless, highly poisonous gas released to the atmosphere mainly by anthropogenic sources such as biomass burning [1], industrial processes and vehicle exhausts [2], but also found in cigarette smoke [3]. Mean mixing ratios of HCN in the unpolluted lower troposphere are typically around 200 parts per trillion by volume (pptv) [1].…”
Section: Introductionmentioning
confidence: 99%